2017
DOI: 10.1021/acs.jafc.7b03252
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Ameliorates Tau Hyperphosphorylation at Ser396 Site and Oxidative Damage in Rat Hippocampal Slices Exposed to Vanadate: Implication of ERK1/2 and GSK-3β Signaling Cascades

Abstract: The objective of this study was to investigate the effect of resveratrol (a natural polyphenolic phytostilbene) on tau hyperphosphorylation and oxidative damage induced by sodium orthovanadate (NaVO), the prevalent species of vanadium (vanadate), in rat hippocampal slices. Our results showed that resveratrol significantly inhibited NaVO-induced hyperphosphorylation of tau at the Ser396 (p-S396-tau) site, which is upregulated in the hippocampus of Alzheimer's disease (AD) brains and principally linked to AD-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…Resveratrol decreases the amyloidogenic cleavage of APP, enhances clearance of amyloid beta-peptides and reduces Aβ aggregation [ 234 , 235 ]. It inhibits the hyperphosphorylation of tau protein at Thr181 in a dose-dependent manner via suppression of the activity of glycogen synthase kinase (GSK-3β) and calmodulin-dependent protein kinase II (CaMKII) [ 236 ], and at Ser396 through a yet unknown mechanism [ 237 ]. In addition, it significantly induces protein phosphatase 2 A (PP2A) activity thereby reducing tau phosphorylation at PP2A-dependent epitopes [ 238 ].…”
Section: Prevention and Treatment Of Nddsmentioning
confidence: 99%
“…Resveratrol decreases the amyloidogenic cleavage of APP, enhances clearance of amyloid beta-peptides and reduces Aβ aggregation [ 234 , 235 ]. It inhibits the hyperphosphorylation of tau protein at Thr181 in a dose-dependent manner via suppression of the activity of glycogen synthase kinase (GSK-3β) and calmodulin-dependent protein kinase II (CaMKII) [ 236 ], and at Ser396 through a yet unknown mechanism [ 237 ]. In addition, it significantly induces protein phosphatase 2 A (PP2A) activity thereby reducing tau phosphorylation at PP2A-dependent epitopes [ 238 ].…”
Section: Prevention and Treatment Of Nddsmentioning
confidence: 99%
“…The phosphorylated GSK-3β at Ser9 site negatively regulates GSK-3β protein activity by causing the N-terminal tail of GSK-3β selfassociation in the primed-substrate binding pocket, thus diminishing primed-substrate phosphorylation by GSK3β. [38][39][40][41] Our result showed that SCA significantly increases the phosphorylation of GSK-3β at Ser9 site and decrease that of GSK-3β at Tyr216, therefore reducing the hyperphosphorylation of Tau in the hippocampus of AD mice. As a result, SCA improved the learning and memory ability and exhibited an anti-AD activity in AD mice (Figure 8).…”
mentioning
confidence: 49%
“…Furthermore, vanadate increases Akt kinase activity and causes its phosphorylation at Ser473 and Thr308, consequently increasing the number of cells at the synthesis (S) phase and transition from gap 1 (G 1 ) to S phase through the E2F-pRb pathway in normal C141 cells [247]. Other studies show that vanadium compounds stimulate kinases in the signal transduction pathways used by insulin beyond the insulin receptor (IR) and the substrate IRS-1, and secondarily, the phosphoinosidide 3 kinase (PI3K), Akt, MAPK pathways (mainly, ERK pathways) together with the activation of the S6 kinases, hence playing an anti-diabetic and anti-lipolytic role, with concomitant insulin-like effects [248][249][250][251][252][253][254][255][256]. Vanadate also stimulates the IRS-1 phosphorylation, the PI3K activity, the ERK signaling pathway, and the p70s6k and p90rsk kinases independently of IR-tyrosine phosphorylation, which in turn phosphorylate and regulate the activity of several transcription factors related with cell proliferation and glycogen synthesis [257][258][259].…”
Section: Kinasesmentioning
confidence: 99%